A lethal mouse model for evaluating vaccine-associated enhanced respiratory disease during SARS-CoV-2 infection - Iwata-Yoshikawa, Naoko; Shiwa, Nozomi; Sekizuka, Tsuyoshi; Sano, Kaori; Ainai, Akira; Hemmi, Takuya; Kataoka, Michiyo; Kuroda, Makoto; Hasegawa, Hideki; Suzuki, Tadaki; Nagata, Noriyo (Science advances, 2022)
Eosinophilic immunopathology was induced by T H 2-shifted immune response and inadequate neutralizing antibody in BALB/c mice. One safety concern during severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine development has been the vaccine-associated enhanced disease, which is characterized by eosinophilic immunopathology and T helper cell type 2 (T H 2)–biased immune responses with insufficient neutralizing antibodies. In this study, we established a lethal animal model using BALB/c mice and a mouse-passaged isolate (QHmusX) from a European lineage of SARS-CoV-2. The QHmusX strain induced acute respiratory illness, associated with diffuse alveolar damage and pulmonary edema, in T H 2-prone adult BALB/c mice, but not in young mice or T H 1-prone C57BL/6 mice. We also showed that immunization of adult BALB/c mice with recombinant spike protein without appropriate adjuvant caused eosinophilic immunopathology with T H 2-shifted immune response and insufficient neutralizing antibodies after QHmusX infection. This lethal mouse model is useful for evaluating vaccine-associated enhanced respiratory disease during SARS-CoV-2 infection and may provide new insights into the disease pathogenesis of SARS-CoV-2.